Challenges in measuring the state of the environment in developing countries: a literature review - Katharina M. K. Stepping (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
A decent environmental quality is a necessary condition for survival of humankind in general and human development in particular. Environmental pollution is a great challenge in developing countries, where especially the poorest are most likely to suffer. Reflecting the state and the dynamics of the environment is essential for science and policy advice. Environmental indicators capture the physical, biological or chemical characteristics of the environment. Environmental composite indicators merge several environmental indicators in order to summarise the multifaceted state of the environment at national level into one single score. These composite indicators allow for cross-country comparisons. The analysis here includes four cross-country composite indicators: the Environmental Vulnerability Index, the Environmental Performance Index, its predecessor the Environmental Sustainability Index and the Ecosystem Wellbeing Index. In addition, the dimension Environmental Wellbeing of the Sustainable Society Index and the Living Planet Index are analysed. Currently, the latter has mainly been constructed at a global scale with only limited availability at national level. The principal questions addressed in this paper are: What cross-country environmental composite indicators exist? To what extent are they suited to measuring the state and the dynamics of the environment? and, How useful are they for developing countries? This analysis is the first comprehensive comparison of cross-country environmental composite indicators, evaluating their conceptual and methodological strengths and weaknesses. The conceptual assessment focuses on content-related aspects. It evaluates whether the individual indicator is an appropriate approximation suited to reflect dimension and composite, respectively. The technical assessment focuses on technical issues of constructing a composite indicator such as imputation of missing data, normalisation, weighting and aggregation as well as coherence. Third, the analysis evaluates how useful these environmental indices are within the context of developing countries.
Keywords: 330; Umwelt; Ökosysteme und Ressourcen